ANTESEDEN DAN IMPLIKASI ATTITUDE TOWARD GREEN PRODUCT PADA INTENSI KONSUMEN: EKSPANSI MODEL DAN KONTEKS PRODUK MENSTRUAL CUP - Rofianto, Whony; Pratami, Annisa Sekar; Sabrina, Manda (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
This research is an expansion of the attitude toward green product model that has been tested in previous studies. This expansion model examines the effect of perceived value, perceived health benefits, health consciousness, environmental attitude, value orientation and eWOM on attitudes toward green products. Furthermore, the impact of continued attitude toward green products on willingness to pay and intention to recommend was also tested, as well as the impact of willingness to pay on purchase intention. This study also seeks to add to the generalization aspect of the attitude toward green product model by testing in the context of menstrual cup products as one of the green products that is still rarely studied in the marketing literature. Empirical data were collected from 99 samples of female respondents who knew about menstrual cup products, as an environmentally friendly substitute for sanitary napkins. Data were collected as primary data through a survey using an online questionnaire. Measurement model estimation and structural model estimation for hypothesis testing were carried out using the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. The estimation results of the inner model indicate a positive influence of perceived value and electronic word of mouth on attitudes toward green products. Attitude toward green products has also been shown to have a positive effect on willingness to pay and intention to recommend. Furthermore, willingness to pay has also been shown to have a positive effect on purchase intention. Meanwhile, the positive influence of four other exogenous variables, namely health consciousness, environmental attitude, value orientation and perceived health benefits on attitudes toward green products was not proven in this study.